ФІНАНСОВЕ ЗАБЕЗПЕЧЕННЯ СОЦІАЛЬНО-ЕКОНОМІЧНОГО РОЗВИТКУ РЕГІОНУ - Дмитровська , В.С.; Солоджук, Т.В.; Максимів, М.С. (Актуальні проблеми розвитку економіки регіону, 2019)
The research of financing the socio-economic development of the region at the expense of local budgets was conducted. Particularly, the conceptual foundations of socio-economic development budget financing have been further developed in terms of determining the directions of using resources that ensure the effectiveness of socio-economic development, systematic financial instruments of social development of the region, and supplemented in the allocation of grants and programs of the State Fund for Regional Development. On the basis of the analysis of budget expenditures, the analysis of financial support of socio-economic development of Ukraine and Ivano-Frankivsk region was carried out. In particular, the expenditures of the general and special fund of the Ivano-Frankivsk regional budget for financing the main directions of socio-economic development of the region were analyzed, the main trends were identified and problems were identified. Despite of important tasks that local governments face up when formulating and using development budgets, they are now mostly used to simplify individual budgetary procedures. In addition, the miserable sumes of local budget development revenues are directed, for the most part, to capital expenditures, to the repairs of social facilities, but not to investments in socio-economic development programs. Therefore, the development budget, as a mechanism for making budget investments, needs to be reformed and improved, due to the limitations on filling this fund with financial resources, the inefficient mechanism for its use and control over the level of efficiency. The state of socio-economic development of Ukraine can be concluded on the basis of statistical indicators characterizing trends in the social and economic spheres. Based on the data of the State Statistics Service, the importance of these indicators in 2015 – 2018 was highlighted. This helped to indicate a number of positive trends within the economic component of socio-economic development and the negative dynamics of some social indicators. It allowed justifying recommendations for improving the effectiveness of financing the socio-economic development of the region.